Pengembangan Media Bandsink Dalam Pembelajaran Matematika Materi Bangun Datar Kelas IV Sekolah Dasar - Hapsari, Nunky Arina; Arisyanto, Prasena; Agustini, Ferina (Universitas Negeri Makassar, 2024)
This research aims to create interactive learning media with Articulate Storyline 3 multi-sided flat shape material for 4th grade elementary school students. This research was triggered by the results of interviews and observations at SDN Bugangan 01 which showed that there were limitations and a lack of optimal use of learning media. Therefore, researchers designed interactive learning media to overcome these problems. The approach applied is Research and Development (R&D) through the ADDIE (Analysis, Design, Development, Implementation and Evaluation) model. Data was collected using interviews, questionnaires and documentation studies. Learning media is assessed by material and media experts, then tested on students and teachers for further validation. The research results show that learning media has been validated by media experts with an average validity of 98.85%, and material experts with an average validity of 89.55%. From this description, it can be concluded that interactive learning media using Articulate Storyline 3 is proven to be valid, easy to use, and effective in learning, especially multi-sided plane material.